The Mandate and Powers of the Regional President in Kurdistan-Iraq - Rahman, Avin Khalid Abdl; Sheikho, Ranjbar Jamil (Journal of Legal and Political Studies, 2015)
Kurdistan Region President is supreme head of the executive power, which represents the region both internally and externally and is elected directly by the citizens region of the for a period of four years, and has re-nomination for another two sessions in accordance with the Law presidency of the region No. 1 for 2005 average.President of the region practiced a range of powers of the legislature is to turn the issue of law and ratify it, to his role in the call parliament to convene, and also has executive authority as chief executive he enjoys issuing decrees and The appointment of the owners of the top positions Such as the positions of Prime Minister and those with special grades and also is the general commander of the Regional Guard (Peshmerga forces) and enjoy the region's president judicial powers of appointment of judges and the issuance of a special pardon to ratify the death penalty, in addition to the above, there are other powers of the exercise is to declare a state of emergency and issue decrees that have the force of law and coordination between the federal and region authorities, and we dealt with research During the first two sections researchers in the mandate of the president of the region in the second researchers in the powers of the president of the region.
Keywords: supreme head; executive power; parliament; judicial powers